A simple method to evaluate the toxic effects of Prorocentrum lima extracts to fish (sea bass) kidney cells. (December 2022) - da Silva, Cesar Aparecido; Mafra, Luiz Laureno; Rossi, Gustavo Rodrigues; da Silva Trindade, Edvaldo; Matias, William Gerson
Abstract: The diarrhetic shellfish toxins (DSTs) okadaic acid (OA) and its analogues — the dinophysistoxins (DTXs) — are produced by dinoflagellates such as Prorocentrum lima and can bioaccumulate in filter-feeding organisms as they are transferred through the food web. Although there is no assessment of the harmful effects of these toxins on the fish's immune system, this study developed a primary culture protocol for kidney cells from marine fish Centropomus parallelus and evaluated the immunotoxic effects to P. lima extracts containing DSTs. The cells were obtained by mechanical dissociation, segregated with Percoll gradient, and incubated for 24 h at 28 °C in a Leibovitz culture medium supplemented with 2% fetal bovine serum and antibiotics. The exposed cells were evaluated in flow cytometry using the CD54 PE antibody. We obtained >5.0 × 10 6 viable cells per 1.0 g of tissue that exhibited no cell differentiation. Exposure to 1.2 or 12 ng DST mL −1 stimulated the immune system activation and increased the proportion of activated macrophages and monocytes in 48 to 52% and in 127 to 146%, respectively. The protocol proved to be an alternative tool to assess the immunotoxic effects of DST exposure on fish's anterior kidney cells. Highlights: A protocol for primary culture of sea bass anterior kidney cells was developed. Kidney cells were exposed to Prorocentrum lima extracts containing diarrhetic toxins. Macrophage and monocyte cell population increased due to exposure to algal extract. Compounds contained in the microalgal extract can act as an inflammatory agent. Potential application to assess the immune system cells of fish exposed to environmental pollutants.